2020
DOI: 10.1371/journal.pone.0226833
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Allium hookeri on gut microbiome related to growth performance in young broiler chickens

Abstract: Healthy food promotes beneficial bacteria in the gut microbiome. A few prebiotics act as food supplements to increase fermentation by beneficial bacteria, which enhance the host immune system and health. Allium hookeri is a healthy food with antioxidant and anti-inflammatory activities. A. hookeri is used as a feed supplement for broiler chickens to improve growth performance. Although the underlying mechanism is unknown, A. hookeri may alter the gut microbiome. In the current study, 16S rRNA sequencing has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 52 publications
1
19
0
7
Order By: Relevance
“…As we enter the post-antibiotic era, plant extracts have shown extremely promising results in terms of zootechnical parameters, immune modulation, and reducing the negative effects of pathogenic challenges, especially with enteric infections. Recent studies have shown that dietary phytochemicals can alter the gut microbiome and modulate mucosal immunity [ 60 , 61 ]. Phytochemicals in general are easy to deliver in animal feed and can be used in solid, dried, and ground forms or as extracts (crude or concentrated), and can also be used as essential oils (EOs; volatile lipophilic substances obtained by cold extraction or steam/alcohol distillation) and oleoresins (extracts derived by non-aqueous solvents), depending on the process used to derive the active ingredients.…”
Section: Individual Seminar Sessionsmentioning
confidence: 99%
See 2 more Smart Citations
“…As we enter the post-antibiotic era, plant extracts have shown extremely promising results in terms of zootechnical parameters, immune modulation, and reducing the negative effects of pathogenic challenges, especially with enteric infections. Recent studies have shown that dietary phytochemicals can alter the gut microbiome and modulate mucosal immunity [ 60 , 61 ]. Phytochemicals in general are easy to deliver in animal feed and can be used in solid, dried, and ground forms or as extracts (crude or concentrated), and can also be used as essential oils (EOs; volatile lipophilic substances obtained by cold extraction or steam/alcohol distillation) and oleoresins (extracts derived by non-aqueous solvents), depending on the process used to derive the active ingredients.…”
Section: Individual Seminar Sessionsmentioning
confidence: 99%
“…With an increasing understanding of the complex intestinal ecosystem and the critical roles of the microbiota in shaping the host immune response as well as gut health [ 60 , 61 , 63 ], a multifaceted approach using synergistic feed additives may be more effective to reduce the disease effects of complex pathogens such as Campylobacter . A multi-pronged approach that combines strategies to reduce C. jejuni cecal colonization in poultry gut, inhibit its survival in poultry products, and reduce its environmental persistence during poultry processing by using various phytochemicals was shown to be an effective nonantibiotic method to reduce the risk of human infections [ 64 , 65 , 66 ].…”
Section: Individual Seminar Sessionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that supplementation with Allium hookeri leaves produced modulation of GM in broilers [101]. In addition, the addition of onion powder to the diet of broilers caused a significant reduction in E. coli population and the increase of Lactobacillus and Streptococcus species, achieving an improvement in the gut histomorphology [96].…”
Section: Discussionmentioning
confidence: 98%
“…Lachnospiraceae and Ruminococcaceae are the most abundant Firmicute families in the gut environment,and Lachnospiraceae was reported to be depleted in inflammatory bowel disease (Biddle et al 2013 ), an observation which might indicate that Lachnospiraceae is negatively connected with inflammatory. Lachnoclostridium and Ruminococcaceae have also been reported to be strongly linked to the regulation of the immune system (Lee et al 2020 ). In the present study, the significant decrease in the abundance of the Lachnospiraceae _FE2018_group and Lachnospiraceae_UCG -001 in BD might also imply a role for Lachnospiraceae in BD via an increase in inflammation.…”
Section: Discussionmentioning
confidence: 99%